Seleção sexual e hierarquia social em peixes - Gonçalves-de-Freitas, Eliane [UNESP]; da Silva Castro, André Luis [UNESP]; Carvalho, Thaís Billalba [UNESP]; de Mendonça, Francine Zocoler [UNESP] (Oecologia Australis, 2009)
Sexual selection is a crucial element to understand behavioral evolution. Teleost fish have been considered as good models for research on sexual selection in the last decades due to their variety of sexual behavior. Female fish can choose males based on body and behavioral traits, such as body size, body color, ornaments, territorial quality, nest size and courtship behavior. Choices are based upon several types of sensorial inputs, such as visual, chemical, sonorous and electrical signals. Intrasexual selection also acts on females because they can mate with a dominant individual in male-male competitions. For both approaches, there is an expectation regarding the benefits of sexual selection by means of female choice. However, in several cases females do not choose the dominant male. In this mini-review, we present and discuss both intersexual and intrasexual mechanisms of sexual selection in fish and point out that females do not always choose a male for mating.
Sexual selection and social hierarchy in fishes
Keywords: Communication; Courtship; Morphological traits; Reproductive behavior; Teleost